Liberalism și limitele dreptății (IDENTITĂȚI VS. DREPTURI. CULEGERE COMENTATĂ DE TEORIE ȘI FILOSOFIE POLITICĂ CONTEMPORANĂ, 2026)
This contribution examines Michael Sandel’s reconsideration of the debate between liberalism and communitarianism in the second edition of Liberalism and the Limits of Justice. It argues that justice cannot be fully justified independently of conceptions of the good and challenges the liberal ideal of state neutrality. By discussing issues such as religious freedom, freedom of expression, and moral reasoning, the text defends the view that rights ultimately depend on the moral significance of the ends they serve. This abstract is generated with artificial intelligence.